O-007 Crossing the clot with a micro-catheter during a mechanical thrombectomy: in vitro evaluation of its impact on the distal emboli burden. (22nd July 2018) - Caroff, J; King, R; Arslanian, R; Marosfői, M; Langan, E; Gounis, M; Chueh, J
Abstract : Introduction: Despite high recanalization rates achieved with endovascular treatment of acute ischemic strokes, 1 2 more than 50% of eligible patients will not present a good outcome (mRS 0–2). 3 Parameters that may determine the patient outcomes include: time from puncture to recanalization, 4 the collateral status, 5 the anesthesia regimen, 6 7 blood pressure management, 8 9 and the distal emboli burden. 10 Characterization of distal emboli generated during mechanical thrombectomy (MT) has been performed in our previous studies. 11 12 We herein further investigated the risk of distal embolization associated with microcatheter navigation through the clot. Materials and methods: A contrast-enhanced clot analog was used in an in vitro model system that mimicked a middle cerebral artery occlusion within a complete circle of Willis vascular replica as previously reported. 13 14 The clot was crossed with one of the following microcatheters: Pro18, XT27 or 3 Max. The emboli generated during the procedure of a size >500 µm were collected and measured with a caliper. The Coulter principle was used to characterize emboli with a size <500 µm. Results: The use of Pro18 and XT27 resulted in a significant reduction of visible particles (size >500 µm) as compared with the 3 Max catheter (p<0.03; Mann Whitney test) (figure 1). For the size range between 8 to 200 µm, Pro18 generated 18% less particles than XT27 (p>0.05). When compared with previously published data, 14 it was found that the clot crossing maneuver accounts approximately for 12% of the total number of small emboli induced during a stent retriever-mediated MT procedure via a balloon guide catheter. Conclusions: Clot crossing maneuver has a significant impact over the total amount of small particles induced during MT. Smaller microcatheter sizes should be favored when possible. References: Saver, et al. N Engl J Med 2015. Dargazanli, et al. American Journal of Neuroradiology 2017. Goyal, et al. Lancet 2016. Saver, et al. JAMA 2016. Nave, et al. Stroke 2018. van den Berg, et al. Stroke 2015. Brinjikji, et al. American Journal of Neuroradiology 2015. Mistry, et al. J Am Heart Assoc 2017. Goyal, et al. Neurology 2017. Gratz et al. American Journal of Neuroradiology 2015. Chueh et al. Stroke 2013. Chueh et al. Intervent Neurol 2017. Chueh et al. Journal of NeuroInterventional Surgery 2017. Chueh et al. Journal of NeuroInterventional Surgery 2016. Disclosures: J. Caroff: 1; C; Educational scholarships from Medtronic Neurovascular and Microvention/Terumo. R. King: None. R. Arslanian: None. M. Marosfői: None. E. Langan: None. M. Gounis: None. J. Chueh: None.